Exploratory laboratory study of lateral turbulent diffusion at the surface of an alluvial channel - Chamberlain, Adrian Ramond, author; Sayre, William, author; Colorado State University, United States Geological Survey, publisher (Colorado State University. Libraries, 1963)
In natural streams turbulent diffusion is one of the principal mechanisms by which liquid and suspended-particulate contaminants are dispersed in the flow. A knowledge of turbulence characteristics is therefore essential in predicting the dispersal rates of contaminants in streams. In this study the theory of diffusion by continuous movements for homogeneous turbulence is applied to lateral diffusion at the surface of an open channel in which there is uniform flow. An exploratory laboratory investigation was conducted in which the lateral dispersion at the water surface of a sand-bed flume was studied by measuring the lateral spread from a point source of small floating polyethylene particles. The experiment was restricted to a single set of flow and channel geometry conditions. The results of the study indicate that with certain restrictions lateral dispersion in alluvial channels may be successfully described by the theory of diffusion by continuous movements. The experiment demonstrates a means for evaluating the lateral diffusion coefficient, and also methods for quantitatively estimating fundamental turbulence properties such as the intensity and the Lagrangian integral scale of turbulence in an alluvial channel.
CER61ARC66.
September 1963.
Keywords: Diffusion; Channels (Hydraulic engineering)